FROM INFLUENCER CREDIBILITY TO BRAND ADVOCACY: THE MEDIATING ROLE OF PURCHASE INTENTION IN SOCIAL COMMERCE (Contemporary Journal of Social Science Review, 2025)
This study examines the impact of social media influencer religiosity and expertise on brand advocacy, using purchase intention as a mediating mechanism. PLS-SEM was used to evaluate the associations among 400 social media users. The findings reveal that influencer religiosity and expertise have a considerable impact on enhancing brand support, and that the benefits are mediated, to some extent, by customer purchase intentions. The findings underscore the relevance of influencer qualities in shaping customer behavior, citing purchase intention as a critical pathway for translating influencer reputation into brand-supporting behavior. These findings provide meaningful advice for marketers looking to optimize influencer initiatives in social commerce.